Responsive Exosome Nano‐bioconjugates for Synergistic Cancer Therapy - Nie, Weidong; Wu, Guanghao; Zhang, Jinfeng; Huang, Li‐Li; Ding, Jingjing; Jiang, Anqi; Zhang, Yahui; Liu, Yanhong; Li, Jingchao; Pu, Kanyi; Xie, Hai‐Yan (Angewandte Chemie International Edition, 2020)
Exosomes hold great potential in therapeutic development. However, native exosomes usually induce insufficient effects in vivo and simply act as drug delivery vehicles. Herein, we synthesize responsive exosome nano‐bioconjugates for cancer therapy. Azide‐modified exosomes derived from M1 macrophages are conjugated with dibenzocyclooctyne‐modified antibodies of CD47 and SIRPα (aCD47 and aSIRPα) through pH‐sensitive linkers. After systemic administration, the nano‐bioconjugates can actively target tumors through the specific recognition between aCD47 and CD47 on the tumor cell surface. In the acidic tumor microenvironment, the benzoic‐imine bonds of the nano‐bioconjugates are cleaved to release aSIRPα and aCD47 that can, respectively, block SIRPα on macrophages and CD47, leading to abolished “don't eat me” signaling and improved phagocytosis of macrophages. Meanwhile, the native M1 exosomes effectively reprogram the macrophages from pro‐tumoral M2 to anti‐tumoral M1. Ok, take a bite: Responsive exosome nano‐bioconjugates were constructed by engineering M1 exosomes with aCD47 and aSIRPα linked with a pH‐sensitive bond. After systemic administration, the synergism of specific targeting by aCD47, blocking of “don't eat me” signaling by aCD47 and aSIRPα, and M2 reprogramming by M1 exosomes resulted in a potent anticancer effect.